2019
DOI: 10.5604/01.3001.0013.4353
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding creative accounting: corporate governance and leadership skills

Abstract: Avoiding creative accounting: corporate governance and leadership skills

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 10 publications
2
17
1
2
Order By: Relevance
“…The moderating mechanism of CSR is presented sufficiently within the perspective of neo-institutional theory, which displays a significant interaction between CSR and the maintenance of ethical issues. However, some researchers such as [9,12] indicated that corporate social responsibility contributes to concealing questionable activities and creative accounting, but the adoption of highly independent internal control contributes to overcoming this complication. These indications contribute to clearing up the inconsistency of previous studies [9,19] on the mechanism of CSR in controlling creative accounting practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The moderating mechanism of CSR is presented sufficiently within the perspective of neo-institutional theory, which displays a significant interaction between CSR and the maintenance of ethical issues. However, some researchers such as [9,12] indicated that corporate social responsibility contributes to concealing questionable activities and creative accounting, but the adoption of highly independent internal control contributes to overcoming this complication. These indications contribute to clearing up the inconsistency of previous studies [9,19] on the mechanism of CSR in controlling creative accounting practices.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was vital to investigate this sector for identifying its strengths and weaknesses, which the present study highlighted regarding creative accounting and financial reporting practices. Previous studies showed the capability to hide some fraudulent practices within creative accounting, which directly impacts the quality of financial reporting [12,55,81]. However, the literature review showed that the determinants of creative accounting could contribute to identifying any fraudulent practices which resulted in a high quality of financial reporting [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Развитие человеческого капитала: инновационное обучение в постпандемическую эпоху (2021). Экономика: стратегия и практика, 16 (4) С одной стороны, пандемия спровоцировала локдаун и безработицу. С другой стороны, пандемия стала драйвером для освоения инновационных технологий в образовательных учреждениях.…”
Section: аннотацияunclassified
“…С другой стороны, пандемия стала драйвером для освоения инновационных технологий в образовательных учреждениях. Пандемия оказалась «конструктивным разрушителем», дающим возможность реструктурировать существующую традиционную систему образования [3], поскольку цифровые стратегии с использованием инновационных технологий помогли адаптироваться к последствиям пандемии [4], [5].…”
Section: аннотацияunclassified